2018
DOI: 10.2147/ndt.s151836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous thrombolysis on length of hospital stay in cases of acute ischemic stroke

Abstract: BackgroundThere are limited data available on factors associated with length of stay (LOS) in cases of acute ischemic stroke according to Poisson analysis, which is more appropriate than other methods.Materials and methodsWe retrospectively reviewed medical summary charts of patients with acute ischemic stroke in 30 hospitals across northeast Thailand, with the main outcome as LOS. Poisson regression was used to examine factors associated with LOS.ResultsWe included 898 patients in the analysis; 460 (51.2%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
3
9
0
3
Order By: Relevance
“…Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 . There is a reciprocal interaction between complications and hospital stay; the infection retards the discharge, and the length of stay increases the risk of infection 26 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 . There is a reciprocal interaction between complications and hospital stay; the infection retards the discharge, and the length of stay increases the risk of infection 26 .…”
Section: Discussionsupporting
confidence: 89%
“…The reperfusion therapy, the investigation of the etiological mechanism, the secondary prevention therapy and early rehabilitation could significantly improve the outcome 4-5 . Otherwise, the occurrence of clinical and neurological complications during hospital stay could influence negatively the patient outcome, delaying discharge 6 and increasing hospital costs 7 and intra-hospital mortality rates 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two-thirds of the patients were discharged NIHSS National Institutes of Health Stroke Scale, mRS modified ranking score P = P value for comparing between the different periods P 1 = P value for comparing between the initial and each periods P 2 = P value for comparing between upon discharge and after 6 months *Statistically significant at P ≤ 0.05 within the first week after admission. Kasemsap and colleagues demonstrated that long hospital stay in AIS patients was found to be associated with intravenous thrombolysis, AF, pneumonia and urinary tract infection regardless of age, stroke severity, or comorbidities [32]. Fjaertoft and colleagues in a 5-year-prospective study suggested that stroke unit care together with early supported discharge (ESD) of AIS patients reduced mortality and increased functional outcome [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study among 898 ischemic stroke patients from 30 hospitals in the Northeastern part of Thailand, it was found that the use of IV thrombolysis is associated with the length of stay. 9…”
Section: Thrombolysis In Thai Patientsmentioning
confidence: 99%